U.S. adjustment policies in trade-impacted industries - Mutti, John.; NPA Committee on Changing International Realities (Washington D.C. : The National Planning association, 1985)
The study shows that overall manufacturing employment grew during the 1970s, despite the increasing relative importance of the service sector of the U.S. economy, and that this trend is likely to persist through the 1980s.
Includes bibliographical references: p. 41-42.
osc 30/01/2019
Loans
Keywords: Industry; Manufacturing